Effect of passion on the athlete engagement of college students specializing in DanceSport: the mediating role of the DanceSport partnership - Huang Ziyou; Yuan Yuxin; Li Xiaofen (Frontiers in Psychology, 2024)
ObjectiveThis research investigates the influence of passion on DanceSport engagement (DSE) among university students specializing in DanceSport, along with the mediating function of DanceSport partnership (DSP).MethodsA survey involving 1,029 participants was conducted using the Passion Scale, Athlete Engagement Questionnaire, and Chinese DanceSport Partnership Scale.ResultsThere were significant positive associations among passion, DSP, and DSE. The path coefficient revealed that passion had a 0.631 (p < 0.001) effect on DSE, a 0.548 (p < 0.001) effect on DSP, and DSP had a 0.217 (p < 0.001) effect on DSE. The direct impact of passion on DSE was 0.725, while the indirect impact was calculated at 0.137, resulting in a total effect of 0.862.ConclusionPassion was identified as an internal motivator enhancing DSE, whereas DSP was found to be an external factor contributing to the increase in DSE levels. DSP played a partial mediating role in the influence of passion on DSE, the more harmonious the DSP, the higher the engagement level. In the future, by understanding the current status and trends of college students’ passion, DSE, and DSP, coaches can timely adjust course content to enhance engagement levels and sports performance by exchanging partners and changing cooperation forms.